3
$\begingroup$

This is the equation, but the result is different from wolframalpha:

$$2^x+4^x=2$$ $$2^x+2^{2x}=2^1$$ $$x+2x=1$$ $$x=\frac{1}{3}$$

WolframAlpha: $x=0$

Where is the error?

$\endgroup$
  • 6
    $\begingroup$ The error is in the step $2^x+2^{2x}=2^1\implies x+2x=1$ which is not true. You can't just take out the exponents this way. $\endgroup$ – Kenny Lau Jun 25 '16 at 7:40
  • 3
    $\begingroup$ To do this question, let $u=2^x$. Then, $4^x=(2^x)^2=u^2$. Then, the equation becomes $u+u^2=2$, which is a quadratic equation. $\endgroup$ – Kenny Lau Jun 25 '16 at 7:40
  • $\begingroup$ why not? Aren't them in the same base? $\endgroup$ – J.Doe Jun 25 '16 at 7:40
  • 1
    $\begingroup$ However, if you have the form $2^a+2^b=2^c$, then when you try to take the log of both sides, you would get $\log_2(2^a+2^b)=c$, but $\log_2(2^a+2^b)\ne\log_2(2^a)+\log_2(2^b)$ $\endgroup$ – Kenny Lau Jun 25 '16 at 7:42
  • 2
    $\begingroup$ $2^x\cdot 2^{2x}=2^1$ implies that $x+2x=1$. Exponentiation turns a sum to a product (and contrariwise taking logarithms turns a product into a sum). There is no formula for $\log(a+b)$ in general. $\endgroup$ – Jyrki Lahtonen Jun 25 '16 at 7:42
8
$\begingroup$

$$2^x+2^{2x}=2$$

Now put $2^x=t$

$$t+t^{2}=2$$

$$t^{2}+t-2=0$$

$$(t-1)(t+2)=0$$

Thus $t=1$ or $t=-2$

$2^x=1$ or $2^x=-2$

Since $2^x>0 $ for all real $x$ , $2^x=1=2^0$

Therefore $x=0$

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

$a^x \cdot a^y=a^{x+y}$ is the identity
you are using $a^x+a^y=a^{x+y}$ which is not correct

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

$2^x + 4^x= 2$ $\Rightarrow$ $2^x (1 + 2^x ) = 2$ $\Rightarrow $ $1 + 2^x = 2 ^{1 - x}$ $\Rightarrow$ $1 + 2^x = 2 ^{- x} \times 2$

Now Set $ y = 2^x$; then we have

$1 + y = y^{-1} \times 2 $ $\Rightarrow$ $y^2 + y -2 = 0$. Which has solutions $y = 1$ and $y = -2$.

$y = -2 $ is unacceptable, because $y = 2^x$ is a positive function. So $y = 2^x = 0$ is acceptable and will give us $ x = 0$. And we are done!

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

we have $$2^{2x}+2^x-2=0$$ and with $$2^x=t$$ you will get $$t^2+t-2=0$$ a quadratic equation to solve.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.